Draft Annual Plan 1987-88 Volume IX Hill Areas Government of Assam - Planning Commission (Planning Commission, 1987)
The Geo-physical condition of both the Districts are as such that the terrain is very much difficult and full of hills and dales. the large nos. of streams and rivulates, which criss-cross the area, necessitate building of bridges and culverts. As a result, it is not only very costly to build the roads but also results in lot of delay in completion of projects. There is only one Railway line passing through these two Districts connecting Cachar District on the South and Nagaon District on the North.
Government of Assam, Development Commissioner for Hill Areas